Knowledge of diabetic foot complication, self-care beliefs and practices among patients attending a tertiary hospital in Eastern Uganda - Olowo, Samuel; Iramiot, Jacob Stanley; Ssenyonga, Lydia V. (International Journal of Africa Nursing Sciences, 2022)
Non-communicable diseases are a stumbling block to global development. Among the diseases, diabetes mellitus in particular, features a major public health problem with increasing prevalence. Foot ulcer ranks first among the complication of diabetes mellitus preceded by cellulitis. This study aimed at determining knowledge about diabetic foot complications, foot care practices, and the beliefs of diabetic patients towards diabetes. Materials and Methods: A cross-sectional survey using a validated structured questionnaire was conducted among 199 Type 2 adult diabetic patients (≥18 years) who visited the hospital clinic and the wards during the study period. Results: More than half that is 118(59.3%) reported not to know that they may develop reduced blood flow in their feet, and 136(68.30%) reported unawareness of smoking as a contributor to reduced blood flow in their feet. Less than half which is 90(45.2%) of the patients reported to dry their feet often after washing, than half that is 96 (48.2%) always inspecting the inside of footwear before putting on, and only 54(27.1 %) of the participants reported never to walk barefooted. The patients’ beliefs on the causes of diabetes included; hereditary, bad dietary habits, inactivity, stress, being fat, punishment from God or gods, and witchcraft. Conclusion: Diabetic patients demonstrated limited knowledge of diabetic foot complications and foot care practices. The patient’s beliefs on the causes of diabetes included; hereditary, bad dietary habits, inactivity, stress, being fat, punishment from God or gods, and witchcraft.
Keywords: Knowledge; Diabetic foot complication; Foot care; Practice; Beliefs; Diabetic patients